Drivers of long-term growth? Assessing the impacts of emerging countries on Sub-Saharan African economies - (:unkn) unknown (My University, 2013)
Panel Cooperation under asymmetric conditions: Africa and the emerging powers, mod. Mamoudou Gazibo http://www.nomadit.co.uk/ecas/ecas2013/panels.php5?PanelID=2017
Keywords: African Research